(untitled) (Modern education and development, 2025)
The objective of this article is to investigate the etymology of English affixes. Methods. The main scientific results are obtained using a complex of general scientific and special research methods, namely: analysis and synthesis of scientific literature on the problems of etymology, word formation, affixation; theoretical generalization and concretization; comparative method and methods linguistic research (contrastive and structural). Results. Etymological analysis plays a significant role in comparative linguistics as it determines the origin of words, records the history of changes in their structure, and explains their modern form In the course of the study one of the main ways of word formation in English, namely affixation was analysed.